Η συμβολή της μελέτης των διαθηκών της παλαιολόγειας περιόδου στην έρευνα των κοσμικών αξιωμάτων και τιμητικών τίτλων - ΣΟΛΩΜΟΥ, Σταυρούλα (Byzantina Symmeikta, 2019)
The present article examines the secular offices, titles and honorific epithets mentioned in testaments. The term testament is used here not only in its strictly legal sense, the disposal of property, but also in the wider one, that of confession, advice, political direction and monastic foundation. The purpose and the demands of the testator dictate the frequency and the kind of offices and titles. Τhey correspond to the government, army and judicial power. Both the highest offices and titles are attested as well as the lowest ones, and they crop up in testaments after the middle of 14th century, when court lists are absent. The reference to the office of basileus is made when the emperor, apart from holding his usual role, is called upon as guardian (trustee) of the testament, restorer or donor of monasteries and receiver of charities. The title despot is the one most commonly mentioned, whereas, the wide use of the honorific epithets doulos, oikeios, pansebastos sebastos is confirmed. Both the social status and the family networking of the testators are obvious